(untitled) (Iraqi Journal of Medical Sciences, 2022)
Background: Despite adequate treatment, about 50% of patients with type 1 diabetes mellitus (T1DM) usually develop a serious complication during their lifetime. The level of hemoglobin A1c (HbA1c) reflects glycemic control, the screening of which is particularly helpful in community-based care settings where tests requiring fasting are not that practical. Objective: To describe the difference in HbA1c level among a sample of children with T1DM and to identify the most common type of compilations and its association with HbA1c and different sociodemographic factors. Methods: A cross sectional study, included 96 children with T1DM, their age ranged between 8-18 years, that attended Medical City Complex in Baghdad in the Pediatrics outpatients Clinic and Endocrine Outpatient Clinic during period from 1st of July 2021 to 30th of October 2021. Results: Males formed 47.9%, 45.8% of them were in school age group, the mean HbA1c level was (10.74±2.974) mg/dl. Employed fathers formed 52.1%. Family history of T1DM was among 13.5% and that of T2DM was among 34.4%. Complication appeared among 71.9% of children, mainly neuropathy found among 50% of them. Children with retinopathy, positive family history have significantly poor controlled DM (last reading HbA1c ?7 mg/dl). Conclusion: HbA1c level in children with T1DM is found to be associated with family history, parents’ education and employment, in addition a significant association with development of retinopathy in those children was also found in this study. Keywords: Type 1 DM, HbA1c, retinopathy Citation: Qasim MF, Tawfeeq ZA. Significance of HbA1c test and different sociodemographic factors in the development of complications in type 1 diabetes in children. Iraqi JMS. 2022; 20(2): 183-190. doi: 10.22578/IJMS.20.2.4